Analysis of noise on board a ship during navigation and manoeuvres. (1st September 2015) - Borelli, D.; Gaggero, T.; Rizzuto, E.; Schenone, C.
Abstract: In the present study, full-scale noise levels measurements on board a Ro-Pax ferry have been carried out in various compartments of the ship, both in stationary conditions (navigation) and during manoeuvres. Noise levels have been surveyed in various categories of spaces located in all decks accessible to both passengers and crew, with the purpose of giving a complete and effective picture of the acoustic climate on board. The measured noise levels have been compared with current and proposed limits for working and living spaces, obtaining a clear identification of the most critical spaces on board the ship both in respect to acoustic comfort and noise exposure of crew during working hours. In cabins, different operating conditions for air conditioning have been tested, to analyse the specific contribution to annoyance of the ventilation noise, which turned out to be in many cases determinant. Transient conditions during manoeuvres entering and leaving harbours have been analysed by spectral time histories in cabins and public spaces close to the main propulsion plant and to bow thrusters. These situations correspond to considerably high levels, which may limit significantly operation during night time. Highlights: Noise surveys are carried out on board a ferry boat in navigation and manoeuvring. Levels are compared with requirements from IMO and other pre-normative formulation. The most critical areas on board are identified. HVAC impact on cabin noise is quantified and procedural aspects are discussed. Noise sources dependence on operating conditions is studied.